AB0325 PREVALENCE OF ANXIETY/DEPRESSION IN PATIENTS WITH RHEUMATOID ARTHRITIS AT THE UNIVERSITY OF CHILE`S CLINICAL HOSPITAL AND THEIR ASSOCIATIONS WITH DISSEASE ACTIVITY INDEXES AND QUALITY OF LIFE. (June 2019) - Chassin-Troubert, Anne Marie; Lillo, Cesar; Prieto, Stephanie; Castro, Ariel; Gatica, Hector; Carrasco, Pilar; Bozan, Francisca; Sabugo, Francisca; Wurman, Pamela; Cruz, Julio; Saavedra, Silvana; Goecke, Annelise
Abstract : Background: Rheumatoid Arthritis is a chronic inflammatory disease with great impact in quality of life. Anxiety and depression could be frequently present in RA patients and may impact the disease activity evaluation. However psicological evaluation or therapy are not part of the standard of care of RA patients. Objectives: To evaluate the prevalence of anxiety/depression in rheumatoid arthritis patients in control at the University of Chile`s Clinical Hospital and to investigate the association of anxiety/depression with disease activity and quality of life. Methods: The Hospital Anxiety Depression Scale (HADS) was applied to measure depression and anxiety in a cross-section patients with RA meeting the ACR/EULAR 2010 criteria in control at the University of Chile`s Clinical Hospital. All patients included gave their inform consent. Demografic characteristics, Disease variables and activity, measure as DAS28-VHS, DAS-28 CRP, CDAI and SDAI and HAQ were evaluated at the same time. Spearmen correlation, Fisher exact test, Chi-Square and Kruskal-Wallis test were used according to variables at evaluation. Statistical analysis was perform by Stata v12.1 sfotware. The study was approved by the Hospital Ethic Review board. Results: 122 patients were enrolled in the study between december 2017 and December 2018. 103 (84.45%) were female. 56 (46%) had depression and/or anxiety according to HADS. 24% of the patients (n=24) had only depression. The severity of the depression symptoms was mild in 71%, moderate in 21% and severe in 8% of the patients. 42%, 40% and 18%of the patients with anxiety (n=55) had mild, moderate and severe anxiety symptoms respectively. The disease activity was significantly higher in patients with as compared to those without anxiety/depression, measure with all of the following indexes: DAS28-VHS (4.33 vs 2.75, p<0.001, DAS-28 CRP (4.13 vs 2.75, p<0.001), CDAI (15 vs 7 p<0.001)and SDAI (17 vs 7.5, p<0.001). The HAQ was also significantly higher in patients with anxiety/depression (1.18 vs 0.29, p<0.01 Conclusion: Depression/anxiety symptoms was very frequent in our cohort of RA patients. The disease activity measure with different indexes and the HAQ was significantly higher in the patients with depression/anxiety. It is possible that psychological factors influence the RA treatment outcomes. Therefore screening and therapy of anxiety and depression should be consider in the regular management of RA patients. References: [1] Michelsen B, Kristianslund EK, Sexton J, Hammer HB, Fagerli KM, Lie E, Wierød A, Kalstad S, Rødevand E, Krøll F, Haugeberg G, Kvien TK. Do depression and anxiety reduce the likelihood of remission in rheumatoid arthritis and psoriatic arthritis? Data from the prospective multicentre NOR-DMARD study. Ann Rheum Dis. 2017 Nov;76(11):1906-1910. Disclosure of Interests: Anne Marie Chassin-Troubert: None declared, cesar Lillo Speakers bureau: Speaker for novartis, Abbvie., stephanie Prieto Speakers bureau: Abbvie, Ariel Castro: None declared, hector gatica: None declared, Pilar Carrasco Speakers bureau: Abbvie, Francisca Bozan: None declared, Francisca Sabugo Consultant for: Abbvie, Novartis, Speakers bureau: abbvie, Pamela Wurman Paid instructor for: Roche, Julio Cruz: None declared, Silvana Saavedra: None declared, Annelise Goecke Consultant for: Roche, abbvie, novartis, Phizer, Paid instructor for: Roche, Speakers bureau: Roche, Novartis, Abbvie, pfizer